The Relationship of Feelings of Loneliness with Symptoms of Social Anxiety in Early Adulthood Due to Changes in Social Dynamics After the Pandemic - Novita*, Regina Sharen; Koesma, Rismiyati E.; Sahrani, Riana (Riwayat: Educational Journal of History and Humanities, 2023)
The COVID-19 pandemic has resulted in restrictions on face-to-face social relationships and activities becoming online activities. This makes young adults find it difficult to build relationships, thus hurting their psychological well-being. This research aims to find the relationship between feelings of loneliness and symptoms of social anxiety in early adulthood due to changes in social dynamics after the COVID-19 pandemic. This type of research is quantitative research with data analysis techniques using correlation tests. This research was conducted on 102 participants with the characteristics of the participants being male and female with an age range of 19-25 years and who were in the transition period from school to college, college to work, or had just changed jobs in the past year. The measuring instrument used in this research was the UCLA Loneliness Scale Ver. 3 to measure feelings of loneliness and the Liebowitz Social Anxiety Scale to measure social anxiety. The results of this research include 1) the results of the correlation test found that there is a fairly strong relationship between the variables of loneliness and symptoms of social anxiety (r = 0.224), which means that there is a relationship between feelings of loneliness and symptoms of social anxiety; 2) no significant correlation was found between the variables of loneliness and social anxiety regarding gender, or loneliness and social anxiety and the living situation after the pandemic can be explained by several complex factors involving individual and environmental dynamics. The role of post-pandemic housing situations may vary significantly depending on how responsive society and individuals are to such changes. So it can reduce levels of loneliness and manage social anxiety without depending on gender and living situation.